At Home He's a Tourist: New Zealand's Architectural Culture in the Eighties - Litterick, Paul (Architectural History Aotearoa, 2009)
I will discuss how architecture was presented and received during the 1980s in the non-specialist print media: magazines and books intended for the general public. During the decade, both the magazine and book publishing industries enjoyed unprecedented growth. The magazine sector saw the dominance of the New Zealand Listener challenged by new titles. Of these, Auckland Metro is the most interesting for architectural culture, since it published regular critiques (by the likes of Peter Shaw, Hamish Keith, David Mitchell and Pip Cheshire) of buildings and of town planning in Auckland. It also documented the rise and fall of the property developers, while arguing for the protection of historic buildings. Equally remarkable, though, is how Metro's interest in the civic aspects of architecture waned during the middle of the decade, as it became less concerned with politics and more with "lifestyle." Its emphasis shifts from public buildings to private houses, and discussion of these houses is centred more on the client than the architect. At the same time, individual architects are pictured as men (and sometimes women) of style, alongside fashion designers and hairdressers. This movement towards lifestyle can be found in other publications of the period and represents a withdrawal from the public square to the private space. Architecture is represented less as a public concern and more as a personal desire - about finding the ideal home. This acquisitive and aspirational interest in architecture is represented most clearly in the Trends family of publications, but also in books of the period. A contiguous development was a growing interest in historic buildings. These are shown both as desirable places to live, but also as representations of New Zealand identity. Old buildings also became an important aspect of New Zealand's tourist industry. One important part of this representation is in the work of art photographers, such as Robin Morrison and Laurence Aberhart. Parallels obviously can be made with the political climate of the decade, with its emphasis on personal gain and the dismantling of the public sphere by privatisation and de-regulation. Equally apparent is the contradiction of New Zealand discovering its heritage at a time when the historic buildings of its cities were being demolished. During the decade, buildings, architects and architecture become totems of larger forces in New Zealand society: of a nostalgia for the recent past, of progress to a brighter future and of a rediscovery of collective identity.